Cluster consensus for inherently nonlinear cooperative networks - CİHAN, ONUR (My University, 2023)
This paper investigates the cluster consensus problem for inherently nonlinear cooperative networks with first and second-order system dynamics. For a first order multi-agent network evolving over a directed graph, not necessarily containing a spanning tree, a sufficient condition based on Lyapunov theory is derived on the single controller parameter so that the system achieves cluster consensus. These stability results are extended to second-order nonlinear systems that utilize two parameters in the distributed control law. Furthermore, the total number of clusters and members of each cluster are explicitly computed from the primary and secondary layer subgraphs of the underlying directed graph. The results are the first in the literature to address the cluster consensus problem for inherently nonlinear cooperative networks evolving over directed graphs that do not contain a spanning tree.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; Biyomedikal Mühendisliği; Kimya Mühendisliği ve Teknolojisi; Havacılık ve Uzay Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Biomedical Engineering; Chemical Engineering and Technology; Aeronautical and Space Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; MÜHENDİSLİK, MEKANİK; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; MÜHENDİSLİK, KİMYASAL; MÜHENDİSLİK, İMALAT; MÜHENDİSLİK, HAVACILIK; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); ENGINEERING; AUTOMATION & CONTROL SYSTEMS; ENGINEERING, MECHANICAL; ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING, CHEMICAL; ENGINEERING, MANUFACTURING; ENGINEERING, AEROSPACE; ENGINEERING, BIOMEDICAL; Fizik Bilimleri; Genel Kimya Mühendisliği; Biyomedikal mühendisliği; Uzay Mühendisliği; Makine Mühendisliği; Endüstri ve İmalat Mühendisliği; Elektrik ve Elektronik Mühendisliği; Control and Systems Engineering; Physical Sciences; General Chemical Engineering; Aerospace Engineering; Mechanical Engineering; Industrial and Manufacturing Engineering; Electrical and Electronic Engineering; cluster consensus; inherent dynamics; multi-agent systems